Inverted odysseys : Claude Cahun, Maya Deren, and Cindy Sherman - Rice, Shelley; Gumpert, Lynn (MIT Press, 1999)
"Claude Cahun, Maya Deren, and Cindy Sherman were born in different countries, in different generations - Cahun in France in 1894, Deren in Russia in 1917, and Sherman in the United States in 1954. Yet they share a deeply theatrical obsession that shatters any notion of a unified self. All three try out identities from different social classes and geographic environments, extend their temporal range into the past and future, and transform themselves into heroes and villains, mythological creatures, and sex goddesses. The premise of Inverted Odysseys is that this expanded concept of the self - this playful urge to "try on" other roles - is more than a feminist or psychological issue